Norbertijner abdijen en landschap in de Nederlanden, 12de-16de eeuw: eenheid of verscheidenheid - Bavel, Bas J. P. van (Norbertijner Abdij-economie en Landschap, 2006)
Keywords: 🇳🇱 netherlands (general)

Norbertijnen en Norbertinessen: turf en landschap - Leenders, Karel A. H. W. (Norbertijner Abdij-economie en Landschap, 2006)
Keywords: 🇳🇱 netherlands (general)

Schakels tussen abdij en stad. De stadshoven van de Norbertijner abdijen in de Nederlanden (ca. 1250 – ca. 1600) - Van Bavel, B.J.P. (Analecta Praemonstratensia, 2000)
The Premonstratensian abbeys were mostly located in the countryside and are often characterised as rural institutions. However, from an early date they developed many links with the cities, which was certainly the case in the Low Countries, an area experiencing a strong process of urbanisation during the late Middle Ages. In the contacts between the abbeys and the cities a crucial role appears to have been played by the houses ('hospicia' or 'mansiones') the abbeys owned in the cities for their own use. These houses, often of considerable size and splendour, fulfilled various functions for the abbeys, functions which developed over time. During the 12th-14th centuries the urban mansions were used mainly for storage, transport and marketing of food stuffs produced on the monastic lands, for instance on nearby granges. With the decline of direct exploitation and the rise of monetarised leasing, however, this function declined. Other functions came more to the fore, such as a base for purchasing goods on the urban market, and a place of residence for negotiations, study or political matters requiring a stay in the city. Also the urban mansions were used more and more as permanent residences, mainly for (retired) abbots. Especially during the religious troubles in the 16th century another function surfaced: that of urban refuge. Thus, these urban houses mirrored the manyfold contacts between abbeys and cities, and also the changes these contacts underwent in time.
Keywords: 🇳🇱 netherlands (general)